Flow stress characteristics and design of innovative 3-steps multiphase control thermomechanical processing to produce ultrafine grained bulk steels - Sumit Ghosh; Jukka Kömi; Suhrit Mula (Materials & Design, 2020)
In the present study, at first flow behavior of Nb–Ti microalloyed and interstitial-free (IF) steels was investigated to know the effects of processing parameters on their microstructural evolution. Then, innovative 3-steps multiphase control rolling schedules have been designed to yield submicron size uniform grains structure and successfully achieved ultrafine ferrite+martensite (0.69–0.78 μm) and ferritic structure (0.83–0.88 μm), respectively, in microalloyed and IF steels. The good combination of yield strength and ductility was achieved for the microalloyed (924 MPa, 13.6% elongation) and IF steel (621 MPa, 19.4% elongation) after rolling as per the designed 3-steps multiphase control deformation schedules. Deformation induced ferrite transformation followed by continuous dynamic recrystallization of the dynamically transformed ferrite is found to be the key mechanism for the formation of the ultrafine grained structure. Due to application of high amount of strains specifically within α+γ phase regime, the α-phase subdivided into several subgrains. These α-subgrains are strongly pinned by the γ/α grain boundaries and thereby restrict the dynamic recovery of the ferrite through reknitting and unravelling subgrain boundaries. On the application of further straining, the misorientation angle between these subgrain boundaries increases continuously through accumulation of the dislocations and finally, ultrafine ferrite grain structure is developed through continuous dynamic recrystallization. Keywords: Low C microalloyed/interstitial-free steels, Flow stress, Deformation induced ferrite transformation, Continuous dynamic recrystallization, Ultrafine ferrite grains, EBSD/TEM analysis